Smoking cessation service in the pharmacy setting - attitudes of pharmacy students, pharmacists and the general public - Milošević Georgiev, Andrijana; Obradović, Dragiša; Krajnović, Dušanka (Archives of Pharmacy, 2023)
Smoking is a global public health problem, and control measures should be implemented in the community so as to reduce the number of smoking-related diseases and healthcare costs. Community pharmacies are ideal places for providing tobacco cessation counselling as a type of public health service, because they are the most accessible health facilities with direct contact with patients. We aimed to examine attitudes towards the implementation of such services, conducting surveys on a sample of pharmacy students (N=300), community pharmacists (N=383) and the general public (N=987) in the Republic of Serbia. The introduction of smoking cessation services at pharmacies was supported by pharmacy students (59.7%), pharmacists (49.2%), and the general public (36.7%). No difference was found between pharmacists` attitudes in terms of their gender, age, level of education and years of experience. We found evidence that pharmacists as public health practitioners were recognized mostly by students (94.3%). The majority of them (86.3%) recognized the need for additional education in order to implement new services, and every third pharmacist recognized a gap in their education. The data indicate the need for directed research in order to explore the educational needs and competences for practicing pharmacists and enable them to perform services such as smoking cessation in the future.
Keywords: smoking cessation; pharmacy services; attitudes; health